The right to life and conflicting interests - Wicks, Elizabeth, LL. M. (Oxford : Oxford University Press, 2010)
This study of the right to life focuses on the legal, as well as ethical, issues raised by the value of life in modern day society. It analyses the development, meaning and value of the fundamental human right to life in the context of its conflicts with other competing interests.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Right to life